Effectiveness of Training and Soft Skills for Enhancing the Performance of Banking Employees - Kaur, Davinder; Batra, Roopali (Prabandhan: Indian Journal of Management, 2018)
Employees are the life blood of an organization, who are believed to have a significant impact on a firm's long-term profitability and growth. Increasing emphasis has been laid by the corporate sector on proper training of employees to equip them with the necessary skills, both technical and soft skills, for enhancing their performance and productivity. Banks are no exception to this. The performance of banks is also dependent upon the performance of their employees. The Indian banking system is a pillar of Indian economy's financial proliferation. Well trained employees with the requisite soft skills are required for effective interpersonal relations, customers' relations, decision making powers, leadership skills, etc. The present research was conducted to determine the effectiveness of training and soft skills in enhancing employee performance in Indian banks. The present study was conducted with the aid of primary data collected from bank employees in Punjab (both public as well as private banks) with the help of a well-structured questionnaire. Correlation and regression techniques were used to study the impact of soft skills and training on employee performance. The results indicated that both training as well as soft skills had a significant impact on employee performance. Interestingly, soft skills were found to have a comparatively greater impact on the performance than training in case of banking employees. The research has strong implications for the banking community and practitioners to understand that not only training, but increasing focus should also be laid on soft skills development for boosting employee performance.